A study of principal’s perceptions regarding time management - Taylor, Kevin C. (Kansas State University, 2007)
The purpose of this study was to identify where secondary public school principals are spending their time while at school by using the population of secondary school principals in Nevada as a study group. A secondary purpose was to identify any statistically significant differences between how Nevada secondary public school principals spend their time in relation to grade configuration: middle school vs. high school, the size of the building they serve, age of the principal, gender of the principal, years of administrative experience and annual yearly progress classification. All secondary principals in the state of Nevada were sent the Time Management for Secondary School Principals’ survey instrument with a (Likert-type) rating scale developed by the researcher. Two statistically significant differences emerged as a result of this study. One, principals of schools with student enrollments of 1,001 students or more rate themselves as spending more time on management items than do principals with student enrollments of 1,000 students or less. Two, females rate themselves as spending more time on instructional leadership items than do their male counterparts. Also, the need to focus on critical components of instructional leadership so that principals can adequately address the 43% of schools not making annual yearly progress in Nevada is discussed. The intent of this study was to identify areas where time was being wasted so that recommendations could be provided to help principals balance their time in a more efficient manner. Principals identified strategies that could prevent focusing all their efforts on managerial issues and allow time for instructional leadership activities. Also, the perception vs. reality and practice vs. theory topics are discussed in relation to time management and instructional leadership. The findings derived from this study are reported in chapter 4 and recommendations to principals regarding effective time management strategies based on responses of Nevada principals are reported in chapter 5.
Keywords: Time management; Principals; Administrators; Secondary; Education, Curriculum and Instruction (0727); Education, Secondary (0533)